(untitled) - Maimon, Elaine P. (New York, 2012)
A Writer's Resource is a tabbed version of the Maimon handbook and includes updated features like "Start Smart" which helps students know where to start and how to navigate all their common writing assignments. The Maimon handbooks support student and instructor success by consistently presenting and using the writing situation as a framework for beginning, analyzing and navigating any type of writing. Start Smart offers an easy, step-by-step process map to navigate three common types of writing assignments. Other new features support critical thinking and deeper understandings of common assignments. Its digital program addresses critical instructor and administrator needs – with adaptive diagnostic tools, individualized learning plans, peer review, and outcomes based assessment. Connect Composition will also fully integrate into the Blackboard CMS for single sign on and autosync for all assignment and grade book utilities.
Keywords: English language,Tiếnh Anh,Tiếnh Anh,English language; Grammar,Handbooks, manuals, etc.,Hùng biện,Sổ tay, sách hướng dẫn, vv,Ngữ pháp,Sổ tay, sách hướng dẫn, vv,Rhetoric,Handbooks, manuals, etc